Perceived urban environment elements associated with momentary and long-term well-being: An experience sampling method approach - Yu-Ru Chen; Atsushi Nakagomi; Masamichi Hanazato; Noriyuki Abe; Kazushige Ide; Katsunori Kondo (Scientific Reports)
Abstract Well-being (WB) extends beyond physical health, as defined by the World Health Organization and encompasses two aspects: (1) long-term WB (LWB), such as overall life satisfaction; and (2) momentary WB (MWB), such as immediate mood. While research has demonstrated a positive association between one’s environment and LWB, limited studies have explored the association between environmental characteristics and MWB. We applied the experience sampling method (ESM) to collect data on location, perceived environmental characteristics, MWB, and LWB of adult participants living in Kashiwa-no-ha area, Kashiwa City, Japan. Structural equation modeling was used to calculate the correlation coefficients between different environments and both MWB and LWB. LWB was positively associated with MWB (standardized coefficient=0.24) and urban elements—cafés/restaurants/bars (0.11), cultural/sports/education facilities (0.04), and public spaces (0.11). Meanwhile, relaxing/clean (0.56) and natural environments (0.14) were associated with higher MWB. Conversely, vibrant environments (−0.14) and being on the move (−0.11) were linked to lower MWB. LWB was positively associated with being at cultural/sports/educational facilities (0.06), and vibrant (0.15) and communicative (0.13) urban settings. MWB was associated with various built environments, emphasizing the need for places like parks and cafés that promote a positive mood, and well-designed transportation and roads. These elements are important for developing urban areas that meet the physical requirements of residents while supporting their emotional and psychological well-being.